2022
DOI: 10.1017/s095026882200139x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of burden of illness measures associated with human (Fluoro)quinolone-resistant Campylobacter spp. infections – a scoping review

Abstract: Campylobacter spp. are one of the most common causes of bacterial gastroenteritis in Canada and worldwide. Fluoroquinolones are often used to treat complicated human campylobacteriosis and strains of Campylobacter spp. resistant to these drugs are emerging along the food chain. A scoping review was conducted to summarize how human (fluoro)quinolone-resistant (FQR; quinolones including fluoroquinolones) Campylobacter spp. infections are characterized in the literature by describing how burden of illness (BOI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…in chickens, many of the Campylobacter spp. isolated from diarrhea patients are quinolone-resistant [ 92 , 93 ]. Genomic analysis showed that the genotypes of some human and avian Campylobacter strains are overlapping.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…in chickens, many of the Campylobacter spp. isolated from diarrhea patients are quinolone-resistant [ 92 , 93 ]. Genomic analysis showed that the genotypes of some human and avian Campylobacter strains are overlapping.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…The use of inappropriate antimicrobials for empirical treatment might contribute to the selection of resistant strains and AMR. Antimicrobial resistance can result from a genetic mutation within the organism or acquiring resistance genes from other organisms following selection pressures in humans and animals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter exposure to antimicrobials is expected to be high. Inappropriate empirical treatment of enteritis in children is common in the study area, and resistant infections result in toxicity, increased morbidity and mortality rates, and a heightened cost of care [12]. Up till now, data on Campylobacter enteritis and antimicrobial susceptibility testing (AST) profiles in children with acute diarrhea in homes with backyard farm animals and/or companion pets is expected to be inaccurate in Ethiopia, due to the use of difficult to compare and/or suboptimal methods for isolation and AST.…”
Section: Introductionmentioning
confidence: 99%